Educating Informal Educators on Issues of Race and Inequality: Raising Critical Consciousness, Identifying Challenges, and Implementing Change in a Youth and Community Work Programme - Jess Achilleos; Hayley Douglas; Yasmin Washbrook (Education Sciences, 2021)
The debate regarding institutional racism and White privilege within higher education (HE) remains prevalent, and higher education institutions (HEIs) are not exempt from the racial equality debate. Youth and Community Work is underpinned by anti-oppressive practice, highlighting a need to educate informal educators on the structural underpinnings of Race and inequlaity, so that they can be challenged in practice to bring about social change. For Youth and Community Workers, this is primarily done through informal education and critical pedagogy. The research aimed to unearth race inequality within the Youth and Community Work programme at Wrexham Glyndŵr University (WGU). Critical reflection methodology was used to deconstruct departmental processes of recruitment, learning and assessment, student voice, and support. Research data was analysed using thematic analysis, determining three themes: critical consciousness, challenge, and change. These are discussed within the framework of Critical Race Theory and critical pedagogy. The research concludes that oppression, and therefore inequality, occurs in the Youth and Community Work programme. Further reading of issues reported in HEIs across the United Kingdom shows that more analysis and deconstruction is needed through CRT. Educating informal educators on issues of race and inequality to raise critical consciousness is one way this can be achieved.